KINERJA DAN EFISIENSI RANTAI PASOK (SUPPLY CHAIN) NANAS DI DESA TANGKIT BARU KECAMATAN SUNGAI GELAM KABUPATEN MUARO JAMBI - Yanita, Mirawati; Wahyuni, Ira (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2021)
This study aimed to analyze the pineapple supply chain's performance and efficiency in Tangkit Baru Village, Sungai Gelam District, Muaro Jambi Regency. The data used in the study was primary data, obtained from direct interviews using questionnaires to 76 respondents consisting of 56 farmers, and 20 marketing agencies involved in pineapple marketing in Tangkit Baru Village from October to December 2019. Pineapple supply chain performance is measured based on marketing efficiency using marketing margin criteria, farmer's share, and profit-to-cost marketing ratio. The results showed that there are five pineapple marketing channels in Tangkit Baru Village that involve marketing actors ranging from farmers, large inter-city traders, village collectors, out-of-pick-up merchants, retailers and consumers. Based on the analysis of marketing efficiency, the marketing channel that has the smallest total margin distribution, the largest farmer share is 100 percent and the total profit-to-cost ratio of 32.2 percent is the 5 marketing channel, so channel 5 is the most efficient marketing channel.